Some reviews on distributed learning in neural networks - Wan Ishak, Wan Hussain (2004)
Training single neural network is a difficult task.In each training session, the network is trained for hundred of epochs and some problem may involve a large amount of variables and data.Thus, training single network is time consuming. Therefore, distributed learning approaches such as hierarchical, multi-stage, parallel neural network computing and multi-modal neural network was introduced.